Exploring the role of the local state in the production and maintenance of space through the delivery of basic services and community responses: the case of N12 highway park, Ekurhuleni metropolitan municipality - Mohale, Nthabiseng (My University, 2018)
This dissertation rests on the argument that spatial production in informal settlements is shaped by state planning processes and the practice of service delivery. The South African urban landscape has been characterized by increasing amounts of informal settlements and the continuities of harsh state responses to these settlements in the form of evictions and relocations. There is a large body of literature on the spatial consequences of informal settlements which is usually centred on poor people-state relations and elaborated through two dynamics. Firstly, the retaliation of residents of informal communities towards the state in the form of Holston’s (1998) insurgent citizenship and protests. Secondly, looking at state responses to informality through policy and clientalist relations, this limiting the attention to the personal experiences of residents living in informality. This ethnographic study explores the theoretical concepts of spatial production and meaning of place for people living in informality. It builds on the work of Henri Lefebvre and Yi Fu Tuan who attribute value to everyday practices and experiences in producing space. These concepts are employed to investigate how the community of N12 Highway Park in the Ekurhuleni Metropolitan Municipality has produced space and made sense of place at the backdrop of their relocation and the kind of basic services the community has received. The study has made use of participant observation, in-depth interviews and focus groups to collect data from community members and state representatives. It describes state responses to informality in communities, with focus placed on the N12 Highway Park informal settlement. It further explores the identities forged by community members in relation to their own perceptions of space and the use of shared state provided facilities; methods behind individual shack renovations; and the establishment of social spaces. The research concludes that service delivery shapes the community’s perceptions of the state and of their lived environment. Furthermore, perceptions of space have shaped spatial production and finding a sense of place through forms of attachment and detachment by community members. This spatial understanding suggests that space is at the centre of people-state relations. Space is therefore shaped by various actors and in the case study of the N12 Highway Park informal settlement: space production as a concept and practice serves as a tool to understand how informal communities give value to their lived environment.
A Dissertation submitted to the Faculty of Engineering and Built Environment, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Master of Urban Studies. Johannesburg, 2018.
Keywords: Local government--South Africa; Municipal government--South Africa